THE HUMAN WORLDVIEW AS A MODELING UNIVERSE (Scientific journal of the Fergana State University, 2024)
The article reflects on the human worldview and the structure of the universe in the text using dictionary tools, the modeling of the whole world. The fact that the formation of a worldview is not the last stage in the formation of a person's personality is evidenced in the analytical aspect. On the basis of the views of philosopher scientists, a solution to the problem is achieved in the principle of linguistic analysis. It is based on the fact that the perception of the world is inherent in a real philosopher, and he can convey it to others, as well as the fact that this is the way to form a new philosophical concept. The points of view are researched based on the analysis of the dream motif used in the works of Togai Murod.